Influencia del programa educativo nacional virtual aprendo en casa en el desarrollo en la expresión oral en niños de cinco años de la Institución Educativa Inicial N° 312 Grillito, Iquitos 2022 - Canayo Del Aguila, Estrellita Evelyn (2024)
This study has been carried out with the purpose of evaluating how the virtual national educational program “I Learn at Home” influences the development of oral expression in 5-year-old children of the initial educational institution No. 312 Grillito Iquitos 2022. The research had a quantitative experimental approach and pre-experimental design. The population was represented by 140 5-year-old students from the Initial Educational Institution No. 312 Grillito 2022. The technique that was applied was observation and the instrument was the observation sheet. The instruments were validated through expert judgment, the objectives were achieved by carrying out statistical hypothesis tests where it was obtained that “I Learn at Home” positively influences the development of oral expression in 5-year-old children of the Initial Educational Institution No. 312 Grillito, Iquitos 2022.